SYNTHESIS OF FUMARONITRILE-CONTAINING QUATERPOLYMER DETERMINATION OF STRUCTURAL AND THERMOMECHANICAL PROPERTIES - Ali Boztuğ; Ersen Yılmaz (Journal of Amasya University the Institute of Sciences and Technology)
In this study, an electron-acceptor monomer Fumaronitrile (FN), and 3 electron-donor monomers; Trans-Anethole (ANE), Vinyl-iso-butylether (VIBE) and Trans-Stilbene (Stb) were polymerized by free radical polymerization and charge transfer complex (CTC) mechanism. Fumaronitrile content ratio, FT-IR, H-NMR, average molar weight, thermal and mechanical analyzes of the obtained FN-ANE-VIBE-Stb quaterpolymer were performed. The synthesized quaterpolymer was obtained in resin form. The rate of fumaronitrile in the chain was determined as approximately 50%. The thermal and mechanical properties of the obtained quaterpolymer were better than some common polymers.